Outcomes of a High-Volume Organ Procurement Organization in the Era of Increasing Donation After Circulatory Death. (December 2022) - Hobeika, Mark J.; Menser, Terri; Myer, Kevin; Lopez, Adriana; Shaikh, Asad F.; Quinn, Lauren; Curran, Chris; Wood, R. Patrick; Ghobrial, R. Mark; Gaber, A. Osama
Introduction: Donation after circulatory death (DCD) is rapidly increasing in the United States. Detailed data outlining the process from referral to organ transplantation is lacking.Project Aims: We sought to quantify differences at each stage along the referral to donation pathway by donor type. Additionally, we examined factors associated with successful DCD organ utilization.Design: This program evaluation analyzed data from a single organ procurement organization in 2018 to assess demographic and clinical predictors of progression through the donation process, including the role of first-person authorization in DCD. Descriptive statistics were examined by donation stage for demographic characteristics using chi-square; univariate and multivariate logistic regression was used to model predictors of utilization and authorization by organ type, respectively.Results: There were 2466 organ donation referrals during 2018, including 575 donations after brainstem death (DBD), 1890 controlled DCD referrals, and 1 uncontrolled DCD referral. Univariate and multivariate logistic regression models highlighted differences in authorization rates by donor type (DCD vs DBD) and by age, race, and ethnicity. Next-of-kin authorization was declined in 23% of first-person authorized potential DCD, highlighting issues related to the role of donor registration in DCD. Pre-mortem heparin administration was predictive of DCD organ utilization; donor age and warm ischemia time of less than 30 min was statistically significantly associated with DCD extra-renal organ utilization.Conclusion: These results provided insight into strategies for increasing authorization and transplantation of organs from DCD donors and identified areas of improvement for process standardization and policy development.